Multi-source excited travelling-wave bowtie antenna based on a meander series of YBCO bicrystal Josephson junctions - Yu, Mei; Wang, Zhenguo; Wang, Bin; Shi, Jin; Liang, Tu-Lu; Jiang, Ruirui; Zheng, Kai; Xu, Weiwei (Frontiers in Physics, 2023)
Series superconducting Josephson junctions (JJs), as terahertz (THz) mixers, have attracted increasing attentions due to their advantages in solving the saturation problem of superconducting mixers, achieving higher mixing harmonics and higher sensitivity in THz band. However, the normal-state resistances of the series JJs are so low that there exists an impedance mismatch between the coupled antenna and the JJs. In this paper, a meander embedding travelling-wave bowtie antenna is proposed for a series of bicrystal JJs. With this antenna, not only the problem of impedance mismatch can be solved, but also more series JJs can be inserted into the antenna. Five and even seven series JJs in the meander match the proposed antenna well. Furthermore, combined current distribution, far-field radiation patterns and parameter study are investigated in the numerical simulation to analyze this antenna.